2011
DOI: 10.1111/j.1365-2915.2011.00970.x
|View full text |Cite
|
Sign up to set email alerts
|

An autodissemination station for the transfer of an insect growth regulator to mosquito oviposition sites

Abstract: A prototype autodissemination station to topically contaminate oviposition-seeking container-dwelling mosquitoes with the insect growth regulator, pyriproxyfen, was developed and tested in the laboratory. Our test subject was the Asian tiger mosquito, Aedes albopictus (Skuse) (Diptera: Culicidae), an urban species that colonizes small-volume cryptic larval habitats and is a skip ovipositor that visits multiple containers. The station consists of a water reservoir to attract gravid females, which is joined to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
94
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(102 citation statements)
references
References 24 publications
(28 reference statements)
7
94
1
Order By: Relevance
“…An obvious opportunity for horizontal transfer between males and females is via coupling during mating and mating attempts. This type of transfer would be similar to that described in previous work with auto-dissemination stations [18]. Indirect transfer to females, via resting surfaces, e.g., water or ovisite sides (Fig.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…An obvious opportunity for horizontal transfer between males and females is via coupling during mating and mating attempts. This type of transfer would be similar to that described in previous work with auto-dissemination stations [18]. Indirect transfer to females, via resting surfaces, e.g., water or ovisite sides (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…Auto-dissemination approaches are being explored for mosquitoes [18,19]. Proposed autodissemination methods are based on the behavior of adult mosquitoes and their attraction to breeding sites, including cryptic sites that human operators may often fail to find.…”
Section: Introductionmentioning
confidence: 99%
“…However, the auto-dissemination of pyriproxyfen, either as a dust or dissolved in water, could be used to treat cryptic and inaccessible breeding sites such as septic tanks and roof gutters. Contaminated mosquitoes could be used to transfer effective doses of pyriproxyfen to such sites (Devine et al 2009, Caputo et al 2012, Gaugler et al 2012. Devine et al (2009) demonstrated that adult Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Devices have been developed to contaminate a skip ovipositing mosquito with an IGR such that the mosquito will transfer the chemical to other ovisites (Caputo et al 2012, Gaugler et al 2012. To maximize effectiveness, the placement of IGR-treated ovisites in the environment should take into account Ae.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge is critical to development of new approaches in Ae. albopictus control where skip ovipositing mosquitoes might be used to distribute an insect growth regulator (IGR) to multiple larval habitats (Caputo et al 2012, Gaugler et al 2012). The distance traveled by contaminated mosquitoes during skip oviposition will determine the extent to which such a control measure can be dispersed utilizing auto-dissemination techniques.…”
mentioning
confidence: 99%